Ceramide activates NFkappaB by inducing the processing of p105 - O'NEILL, LUKE ANTHONY JOHN (The American Society for Biochemistry and Molecular Biology, 1998)
The role of ceramide as a second messenger in tumor necrosis factor (TNF)-mediated signal transduction has been much debated. It is supported by recent reports describing an expanding number of potential targets for this lipid, but is opposed by those describing how ceramide is not necessary for many TNF-mediated cellular events. In this paper, we directly compare the effects of the cell-permeable ceramide analogue, N-acetylsphingosine (C2-ceramide), with TNF, on NFkappaB function, a transcription factor whose activation is central to many TNF-mediated effects. We describe how C2-ceramide failed to drive kappaB-linked chloramphenicol acetyltransferase gene expression in either HL60 promyelocytic or Jurkat T lymphoma cells. Furthermore, it had no effect on TNF-mediated transcription of this reporter gene. However, electrophoretic mobility shift analysis following cell stimulation with this ceramide analogue revealed a dose-responsive activation of NFkappaB, which was not apparent following cell treatment with the inactive dihydro form. Activated complexes from treated cells were shown to contain predominantly the p50 subunit, in contrast to complexes from TNF-treated cells, where both p50 and p65/RelA subunits were present. The specific activation of p50 homodimeric complexes by C2-ceramide, which are known to lack trans-activating activity, was strongly suggested from these data. Further investigations revealed that C2-ceramide had only a marginal effect on IkappaBalpha degradation but strongly promoted the processing of p105 to its p50 product as revealed by immunoblot analysis. The increase in p50 arising from the processing of its p105 precursor was further established from p105/p50 ratios obtained by scanning densitometric analysis of bands from immunoblots. TNF, on the other hand, stimulated both IkappaBalpha degradation and p105 processing, in accordance with previous findings. Furthermore, the effect of TNF on NFkappaB activation was rapid, whereas C2-ceramide required an optimal treatment time of 1 h. Interestingly, TNF was found to increase ceramide in cells but only after a 1-h contact time. Our data therefore suggest that ceramide promotes the activation of NFkappaB complexes that lack transactivating activity by enhanced processing of p105.
PUBLISHED
Keywords: Biochemistry